Utilization of family medicinal plants for health in Ngasem Village - Lina Agustina; Santhyami Santhyami; Putri Agustina; Eriza Putri Ayu Ning Tyas; M. Galih Wicaksono; M. Reisa Andika (Community Empowerment, 2023)
Medicinal plants and traditional medicines since ancient times have played an important role in maintaining health. Traditional medicinal plants become an alternative in the treatment of a disease. The purpose of this community service is to increase public understanding about the use of Family Medicinal Plants (TOGA). The method in this activity is to provide counseling about the types and benefits of family medicinal plants and the provision of medicinal plant seeds to be planted in KWT Ngasem. The result of this activity is an increase in public understanding and interest in the use of TOGA and starting to cultivate it.